Long Hours' Effects on Work-Life Balance and Satisfaction. (23rd June 2019) - Hsu, Ya-Yuan; Bai, Chyi-Huey; Yang, Chien-Ming; Huang, Ya-Chuan; Lin, Tzu-Ting; Lin, Chih-Hung
Abstract : Purpose . In this study, we examined whether the associations between working hours, job satisfaction, and work-life balance are mediated by occupational stress. In addition, we tested whether perceived time control helps moderate the effects of working hours and occupational stress. Methodology. Questionnaires were administered to 369 respondents working in the high-tech and banking industries. Analyses were then conducted on the data. Findings. The analysis revealed significant correlations between long working hours and both occupational stress and work-life balance, as well as between occupational stress and both work-life balance and job satisfaction. In addition, the relationship between working hours and occupational stress exhibited a significantly positive interaction with perceived time control. Value. The results indicate the importance of giving workers greater control over working hours. We therefore recommend that labor laws should be revised as necessary to prevent excessive working hours and enhance work-time flexibility.